Outstanding diversity and microendemism in a clade of rare Atlantic Forest montane frogs - Thomé, Maria Tereza C. [UNESP]; Lyra, Mariana L. [UNESP]; Lemes, Priscila [UNESP]; Teixeira, Laryssa S. [UNESP]; Carnaval, Ana Carolina; Haddad, Célio F.B. [UNESP]; Canedo, Clarissa (Elsevier, 2020)
Distributed across topographically complex landscapes that vary from lowland to high elevation, the Atlantic Forest harbors one of the richest biotas worldwide. Atlantic Forest amphibians are particularly speciose, taxonomic accounts are rising and the group is used as model for biogeographic inference. Past climate-related habitat fragmentation is often invoked to explain diversification, with montane taxa expected to become more widespread during glacial times and restrained at interglacials. In this study we investigate diversification in Ischnocnema lactea and I. holti (Anura: Brachycephalidae), two rare frog species inhabiting Atlantic Forest montane regions in Southeastern Brazil. Previous phylogenetic accounts have suggested uncertain limits between these two sister species. We assembled a multilocus DNA dataset, delimited lineages in this clade, and used ecological niche modeling to explore past and future putative ranges. Assignment analyses and traditional and coalescent phylogenetic methods confirmed the existence of a species complex of Miocene origin comprising nine lineages, most of which show very narrow ranges. Lineages were fully supported as species based in coalescent species delimitation, but the phylogenetic relationships among lineages in higher elevation were unresolved. Models of past ranges suggest extensive suitable areas at the last glacial maximum which, along with phylogenetic uncertainty, are consistent with a hypothesis that climate driven vicariance at higher elevation areas resulted in hard polytomies. Species distribution models under future climates suggest narrower ranges of the lineages relative to now, but no species are currently considered endangered. Overall, our results argue in favor for the reassessment of the taxonomic and conservation status of the I. holti – I. lactea species complex.
Keywords: Amphibians; Conservation; Deep genetic divergences; Elevation; Ischnocnema